Psychotropic drug-prescribing correlates of disorganized speech in Asians with schizophrenia: The REAP-AP study - Yong Chon Park; Min-Soo Lee; Tian-Mei Si; Helen F.K. Chiu; Shigenobu Kanba; Mian-Yoon Chong; Adarsh Tripathi; Pichet Udomratn; Kok Yoon Chee; Andi J. Tanra; Golam Rabbani; Afzal Javed; et al. (Elsevier, 2019)
Background: Although disorganized speech is seen as one of the nuclear features of schizophrenia, there have been few reports of disorganized speech-associated psychotropic drug-prescribing patterns in large samples of schizophrenia patients. Objective: We aimed to examine the prevalence of disorganized speech and its correlates in terms of psychotropic drug prescribing, using the data from the Research on Asian Psychotropic Patterns for Antipsychotics (REAP-AP) study. Method: A total of 3744 patients with the ICD-10 diagnosis of schizophrenia were enrolled from 71 survey centers in 15 Asian countries/areas. An essential criterion of disorganized speech was that it was "severe enough to impair substantially effective communication" as defined in the DSM-5. A binary logistic model was fitted to identify the psychotropic drug-prescribing correlates of disorganized speech. Results: After adjusting for the potential effects of confounding variables, the binary logistic regression model showed that the presence of disorganized speech was directly associated with adjunctive use of mood stabilizers (P < 0.001) and cumulative diazepam equivalent dose (P < 0.0001), and inversely associated with adjunctive use of anti-Parkinson drugs (P < 0.0001). Conclusion: The association between disorganized speech and adjunctive use of mood stabilizers could perhaps be understood in the context of a relationship with impulsiveness/aggressiveness, or in terms of deconstructing the Kraepelinian dualism. Keywords: Asian, Disorganized speech, Mood stabilizers, Schizophrenia